Atomic Layer Deposition for Advanced Electrode Design in Photoelectrochemical and Triboelectric Systems. Issue 4 (20th January 2017) - Su, Jingjie; Li, Zhaodong; Yu, Yanhao; Wang, Xudong
Abstract : As a powerful and versatile thin film deposition technique, atomic layer deposition (ALD) has been increasingly involved in the manufacturing of many energy harvesting and storage devices. Compared to the applications of ALD in lithium ion batteries and supercapacitors, ALD in photoelectrochemical (PEC) electrode and triboelectric nanogenerators (TENGs) development is relatively new. Most current progress in these two promising directions is not quite comprehensively covered. This article intends to summarize the most recent and representative research regarding the application of ALD in the fabrication of PEC electrodes and TENG active materials. We first discuss ALD of nanostructured electrochemically active materials and surface coating for PEC photoelectrodes, and the corresponding influence on solar energy conversion efficiency and electrode stability are discussed and compared. A unique high‐temperature ALD‐based approach, called surface‐reaction‐limited pulsed chemical vapor deposition (SPCVD) is then introduced as a new approach to the synthesis of 3D branched NW architecture, which offers tremendous advantages in photoelectrode design. At last, a new exploration of ALD in the field of mechanical energy harvesting is presented as an effective strategy to modify the dielectric property of polymer thin films for TENG development. Abstract : On the basis of sequential self‐limiting surface reactions, atomic layer deposition is capable of growing high quality, pinhole‐free and conformal thin films as well as 3D nanoarchitectures, promoting advanced design and manufacture of highly‐efficient and extremely‐stable photoelectrochemical electrodes and triboelectric nanogenerators.